The Big Pine Bark Of The Fargoga Valley - D. Sultanov; F. Tokhtasinov; O. G'furova; M. Teshajonova; M. Sodikova (Zien Journals, 2023)
Large pine bark beetle - Scolytus scolytus (Fabricius, 1775) is a polyphagous insect, it is widespread in Eurasia, as well as in all regions of Uzbekistan
Keywords: Large pine bark